Evaluation of Nurses’ Practices towards Care of the newly born Infant Immediately after Birth in Delivery Rooms in Baghdad City Hospitals - Khudhair, Suad H.; Ma’ala, Eqbal G.; Hameed, Numan N. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Every hospital with delivery services should have skilled nurses immediately available for neonatal care, and appropriate equipments should be present at all deliveries. The first hour after birth has a major influence on the survival, future health, and well being of a newly born infant. The nurses have an important role at this time, the care they give during this period is critical in helping to prevent complication. Objectives: The study aims to evaluate nurses’ practices toward care of the newborn infant immediately after birth in delivery rooms and finds the relationship between the nurses’ practices and their demographic characteristics. Methodology: A descriptive study was carried out in 3 teaching hospitals (Al-Yarmouk Teaching Hospital, Al-Karama General Teaching Hospital, and Al-karkh Maternity Teaching Hospital) in Baghdad City, Iraq, from the 22th May 2013 to 30 July 2013. A purposive (non probability) sample of 40 nurses who are working in the delivery room in these hospital. The data was collected through using constructed questionnaire which comprises 44 items and filled by using interview technique. The reliability of the questionnaire was determined through a pilot study and validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient and chi-square. Results: The study results shows that (30.0 %) of the study sample were 36-40 years old, (40.0 %) graduated from medical institute, (75.0%) were married, (32.5%) have more than 16 years of employment in nursing, (30.0 %) have more than 16 years of practices in maternal delivery room,(55%) of them have training session and (72.5%) participate in training session inside of Iraq. The Percentages for total nurses’ practices scores toward care of the newly born immediately after birth includes 25% for physical examination, 30% for neonatal supplies and equipment, 25% for providing warmth and 20% for preventing injury, infection and provide feeding. The study demonstrated that there was poor nurses’ practice about care of the newborn infant immediately after birth in delivery rooms Conclusions: The study comes to the following conclusions: The nurses were poor practices in caring for the newborn babies immediately after birth in delivery rooms.